Profitability Analysis and Asset Structure Against Company Value with Intellectual Capital as Moderation - Oktaviani, Retno Fuji (Universitas Pamulang, 2022)
This study aims to analyse the effect of profitability and Asset Structure on the Value of Companies with Intellectual Capital as Moderation of Empirical Studies on Manufacturing Companies in the Food and Beverage Industry Sub-Sector Listed on the Indonesia Stock Exchange for the 2016-2020 Period. The total population are 32 companies, and the sampling technique with purposive sampling collected sample was 16 companies. This research used analysis multiple linear regression with moderation variable. Statistical software for calculated data is Rstusio. The results showed that profitability and asset structure proved to have an influence on firm value. Variable intellectual capital moderating has also been shown to have a moderate effect on profitability and asset structure on firm value.